海關 데이터로 본 1870年代 長江의 洋船 交易 －九江의 事例를 中心으로 - 김현정; Kim Hyunjung (史叢(사총), 0(112), 2024)
본 논문은 청말 통상항체제의 실상을 파악하기 위한 기초 연구의 일환으로서, 1870년대 구강의 해관자료를 분석하여 양선 교역의 실제적 양상을 고찰하고자 하였다. 구강의 양선 교역은 상해를 중심으로 한 간접 수입과 수·이출의 특징을 보였으며, 이는 장강의 통상항이 지닌 지정학적 성격에 기인한 것으로 볼 수 있다. 또한, 양선으로 이입된 외국상품과 내지산품의 대부분이 구강 및 주변 내지에서 소비되었다는 점에서 내지 수요와의 연동 가능성을 시사한다. 교역 구조는 몇몇 주요 품목에 집중되는 단순한 형태였으며, 상품의 품목별 이입 비율과 이입 추이의 변동은 내지산품에서 더 두드러졌다. 이는 특정 품목의 생산량 증가, 지역적 경기, 기후 환경의 변화 등 다양한 요인에 기인하였으며, 국제교역의 흐름과는 큰 연관성이 없는 것으로 나타났다. 한편, 내지산품 이출 교역에서는 내지자본의 영향력과 내지 수요에 기반한 지역적 교역의 성격이 확인되었으며, 민선에서 양선으로의 운송 수단 및 통상항 간 교역 루트의 전환도 일부 나타났다. 다만, 이러한 전환은 절대적이지 않았으며, 상품의 특성이나 세금 회피 등의 이유로 기존 운송 수단 및 교역 루트가 유지되는 현상도 병존하였다. 마지막으로, 1877년 무호의 개항이 구강의 양선교역에 미친 단기적 영향은 크지 않았으나, 장기적 영향력에 대해서는 추가 연구가 필요할 것으로 보인다. This study aims to investigate the characteristics of the foreign vessel trade in the yangzi River during the late Qing period by analyzing the 1870s Jiujiang Customs data. The findings reveal that the foreign vessel trade in Jiujiang was characterized by indirect imports and exports, with Shanghai serving as the main hub. The geographical nature of the yangzi River treaty ports significantly influenced this trading pattern. The majority of foreign and native goods imported through foreign vessels were consumed in Jiujiang and its surrounding regions, suggesting a potential link to domestic demand. The trade structure was simplistic, with a few key commodities dominating the market. Fluctuations in the proportion and trends of imported goods were more prominent for native products, which can be attributed to various factors such as changes in production volume, regional economic conditions, and climate, rather than international trade flows. The export trade of native products revealed the influence of domestic capital and the nature of regional trade based on domestic demand. Additionally, there was a partial shift in transportation methods and trade routes from native boats to foreign vessels and between treaty ports. However, this transition was not absolute, as existing transportation methods and trade routes were maintained due to factors such as product characteristics and tax avoidance. The short-term impact of the opening of Wuhu in 1877 on Jiujiang's foreign vessel trade was limited, but further research is needed to assess its long-term influence.